Shearing Properties of Epoxy and Epoxy Bitumen as Bonding Material of Asphalt Overlay on Ultra-High Performance Concrete Slab - Dinh, Trung Quang; Tran, Thi Kim Dang; Ngo, Ngoc Quy (Engineering, Technology & Applied Science Research, 2024)
This article discusses the results of direct shear and fatigue shear tests on epoxy resin and epoxy bitumen bonding materials. Shearing properties, including shear strength, shear stiffness, shear energy, and post-failure energy, are analyzed using results from direct shear tests at 30°C and 60°C. The fatigue tests used a direct shearing test with a pulse load of 1 Hz frequency at 60°C to analyze the fatigue life and plateau value based on the ratio of dissipated energy change versus load cycles curve. At 30°C, the shearing properties of the tested epoxy resin were approximately 60-70% higher than those of the tested epoxy bitumen. The epoxy resin possesses an outstanding advantage against the epoxy bitumen at high temperatures when applying the shear energy approach. At 60°C, the shear energy of the epoxy resin was 30.5% higher than that of the epoxy bitumen, while its shear strength and shear stiffness were 18.5% and 79% lower than those of the epoxy asphalt, respectively. The shear fatigue life of the epoxy resin after the energy method was more than ten times that of the epoxy bitumen, and its plateau value was only 10% of the epoxy bitumen. Regression analysis was also performed using fatigue shear test data to provide a fatigue shear equation in the form of an exponential function.